Radiofrequency resection of bronchial tumours in combination with cryotherapy: evaluation of a new technique. Issue 2 (February 1998) - Marasso, A; Bernardi, V; Gai, R; Gallo, E; Massaglia, G M; Onoscuri, M; Cardaci, S B
Abstract : BACKGROUND: A number of treatments, including Nd-YAG laser therapy, brachytherapy, cryotherapy, electrocautery, and photodynamic therapy, can re-open the obstructed bronchial lumen in patients with inoperable obstructive bronchial tumours. None of these is considered to be a "gold standard". METHODS: The results of a retrospective study of 98 patients treated by radiofrequency tissue ablation and subsequent cryotherapy between January 1994 and June 1995 are reported. The patients were divided in two groups according to whether they were treated either after (group 1, n = 50) or before (group 2, n = 48) radiotherapy and/or chemotherapy. Bronchoscopic follow up was performed. The intervention was considered successful if the lumen was opened by > 80% and partially successful if it was opened by > 50%. RESULTS: In group 1 treatment was successful in 60%, partially successful in 32%, and unsuccessful in 8%. The median survival time was five months from the time of bronchoscopic surgery. In group 2 treatment was successful in 66%, partially successful in 21.5%, and unsuccessful in 12.5%, with a median survival time of 14 months from the time of bronchoscopic treatment. Forty patients (24 in group 1 and 16 in group 2) received a Dumon stent. CONCLUSIONS: Radiofrequency bronchoscopic surgery with cryotherapy appears to be a useful technique in the treatment of tracheobronchial obstruction.